Genetic structure and demographic analysis of a true single-population species, Camellia azalea - Ruo-Qiu Wang; Ying Xu; Min Zhang; Gang Hao; Qiang-Min Zhao; Xin-Kai Liu; Xiao-Fei Liu; Bo Yu; Wen-Ju Zhang (BMC Plant Biology)
Abstract Single-population species (SPS) consist of only one natural population and often are at high risk of extinction. Although almost all species must go through this special stage in their evolutionary process, there is little understanding of how SPS survives. Camellia azalea C. F. Wei is a typical SPS, and has precious breeding values for its special flowering period. This study surveyed the age structure and spatial distribution of C. azalea, analyzed its genetic diversity and fine-scale spatial genetic structure (SGS) using microsatellite markers for 629 individuals, and estimated the effect of human disturbances on its population dynamics. Results showed that this species had a relatively moderate genetic diversity (I = 0.989, He = 0.509, and Ho = 0.497), high rate of sapling (~ 35%), and a narrow habitat (~ 6 km long, ~ 10 m wide). Although the construction of dams and roads did not lead to a significant loss of genetic diversity and genetic differentiation (F ST  = 0.0096 ~ 0.0128, N m  = 19 ~ 26), it limited C. azalea’s seed flow (adults, 95 m; juveniles, 60 m), which was a reason for juveniles having a stronger SGS than adults. These results indicate that as an SPS, C. azalea still possesses the potential capacity for self-evolution and regeneration, however, it is at risk of extinction due to its small range, narrow habitat, and human distances. Furthermore, the results are also of enlightening significance to the conservation of other SPS, especially those distributed along the riparian zone.